Gene Correction Reverses Ciliopathy and Photoreceptor Loss in iPSC-Derived Retinal Organoids from Retinitis Pigmentosa Patients - Wen-Li Deng; Mei-Ling Gao; Xin-Lan Lei; Ji-Neng Lv; Huan Zhao; Kai-Wen He; Xi-Xi Xia; Ling-Yun Li; Yu-Chen Chen; Yan-Ping Li; Deng Pan; Tian Xue; et al. (Stem Cell Reports, 2018)
Summary: Retinitis pigmentosa (RP) is an irreversible, inherited retinopathy in which early-onset nyctalopia is observed. Despite the genetic heterogeneity of RP, RPGR mutations are the most common causes of this disease. Here, we generated induced pluripotent stem cells (iPSCs) from three RP patients with different frameshift mutations in the RPGR gene, which were then differentiated into retinal pigment epithelium (RPE) cells and well-structured retinal organoids possessing electrophysiological properties. We observed significant defects in photoreceptor in terms of morphology, localization, transcriptional profiling, and electrophysiological activity. Furthermore, shorted cilium was found in patient iPSCs, RPE cells, and three-dimensional retinal organoids. CRISPR-Cas9-mediated correction of RPGR mutation rescued photoreceptor structure and electrophysiological property, reversed the observed ciliopathy, and restored gene expression to a level in accordance with that in the control using transcriptome-based analysis. This study recapitulated the pathogenesis of RPGR using patient-specific organoids and achieved targeted gene therapy of RPGR mutations in a dish as proof-of-concept evidence. : Jin and colleagues demonstrate that patient-specific iPSC-derived 3D retinae can recapitulate disease progress of retinitis pigmentosa through presenting defects in photoreceptor morphology, gene profile, and electrophysiology, as well as the defective ciliogenesis in iPSCs, iPSC-RPE, and 3D retinae. CRISPR/Cas9-mediated gene correction can rescue not only photoreceptor structure and electrophysiological property but also observed ciliopathy. Keywords: RPGR, photoreceptor, electrophysiology, retinitis pigmentosa, patient-derived iPSCs, retinal organoid, RPE cells, cilium, ciliopathy, disease modeling